The role of venture capital funds in developing innovative activities of the European Union countries - Katarzyna Wierzbicka (Institute of Economic Research (IER), 2017)
Venture capital funds are very important in the development of innovative activity of economic entities. The funds contribute to closing the equity gap in the financing of innovative companies. The purpose of the study is to show the role that venture capital funds play in the development and functioning of business entities in EU companies. DEA (Data Envelopment Analysis), a non-parametric decision making unit (DMU), was used to examine the relationship. The study covered the 2010 and 2015 periods. The results confirm the assumption that venture capital funds operate most effectively in the most innovative economies of the EU.
Keywords: O16; 330; innovativation; venture capital; Innovative activity; efficiency